ANALYSIS OF FACTORS AFFECTING MSMEs INTENTION TO USE PEER-TO-PEER LENDING - Sri Kartika Afini; Rita Rahayu (Jurnal Ekonomi, 2022)
Study this aim to analyze influencing factors _ SMEs' intention to using peer to peer lending as alternative funding for businesses them. Study this use survey method with using online questionnaires. A total of 327 people participated Furthermore, the data is processed with use SmartPLS 3.0. based on data processing found that perception benefit give influence positive and significant to attitude user , perception convenience give influence positive and significant to attitude user , attitude user give influence positive and significant to intention using , and intention use give influence positive and significant to actual use. Research results this expected could beneficial for SMEs in _ choose alternative funding for his efforts .